Virtual congkak learning tool using augmented reality - Shahanaz Natasha, Jamihil @ Jamil (2019)
Nowadays, we live in a life where technology has become a part of our lives. Technology has evolved in many ways where it helps us every day. People cannot see themselves without smartphones, computer and etc. Because of the evolution of technology era, many traditional cultures got lost and being forgotten. Some of it were important where it symbolize ourselves. For an instance, traditional games are the symbol of one’s culture. In Malaysia, we have our own traditional games to identify the identity of each cultures we have such as Malay, Chinese and Indians. From Malay’s culture, Congkak is one of a famous game played among the generation. But due to the technological sophistication, people are more attracted to play mobile games instead of traditional games especially to the younger generation. To overcome this problem, Virtual Congkak Learning Tool in Augmented Reality has been developed. This tool was created for the beginners of Congkak because the young generation may be not familiar with the rules of Congkak at all. So this tool will be helpful for them. And also, the idea of creating this learning tool in an augmented reality environment is to expose and attract these young generations to play traditional games, especially Congkak following the advanced technologies today. This application follows Rapid Application Development (RAD) methodology. Virtual Congkak was built using Unity 3D platform with supports of Vuforia for augmented reality. The result of this project was it meets all the objectives and the main functions worked and met the requirements.